Creating an Effective Conference Presentation: A Reflective Practice on Challenges in Creating an Effective Conference Presentation - Matthew Downing (Journal of Scholarly Engagement)
The purpose of this reflective practice was to examine my conference presentations to K-12 teachers and administrators in order to increase their effectiveness. I have often felt frustrated by my conference presentations not accomplishing their intended objective for the attendees. I possessed a general understanding of the suspected reasons; however, I wanted to identify specifics so that I could implement change through a conference presenting protocol (Appendix A). This reflection occurred through a series of three conference presentations. This allowed me to iterate through each conference presentation, focus on specific areas, and arrive at beneficial insights. Ultimately, this reflective practice demonstrated the need to keep the audience central, narrow the focus, and provide guided assistance with the design thinking process. The lessons learned will assist in creating more effective conference presentations, which can also be applied to additional contexts, such as leading professional development for K-12 teachers.